2007
DOI: 10.1111/j.1551-2916.2007.02029.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Step Sintering of Nanocrystalline ZnO Compacts: Effect of Temperature on Densification and Grain Growth

Abstract: Two-step sintering (TSS) was applied on nanocrystalline zinc oxide (ZnO) to control the accelerated grain growth occurring during the final stage of sintering. The grain size of a high-density (498%) ZnO compact produced by the TSS was smaller than 1 lm, while the grain size of those formed by the conventional sintering method was B4 lm. The results showed that the temperature of both sintering steps plays a significant role in densification and grain growth of the nanocrystalline ZnO compacts. Several TSS reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(101 citation statements)
references
References 36 publications
5
90
0
6
Order By: Relevance
“…Furthermore Zhang et al proposed kinetic window for successful TSS profile. Mazaheri et al [22] confirmed the triple-point drag mechanism for controlled grain growth at the second-step sintering proposed by Chen and Wang [15] by using TEM image of two-step sintered ZnO compacts. ZnO sintered via TSS exhibited excellent I-V characteristics [16,74,76].…”
Section: Sintering Of Zinc Oxidementioning
confidence: 70%
See 2 more Smart Citations
“…Furthermore Zhang et al proposed kinetic window for successful TSS profile. Mazaheri et al [22] confirmed the triple-point drag mechanism for controlled grain growth at the second-step sintering proposed by Chen and Wang [15] by using TEM image of two-step sintered ZnO compacts. ZnO sintered via TSS exhibited excellent I-V characteristics [16,74,76].…”
Section: Sintering Of Zinc Oxidementioning
confidence: 70%
“…TEM images of the ZnO samples sintered (a) using TSS profile with the first-step sintering temperature of 800°C for 60 s and a second-step sintering temperature of 750°C for 72,000 s, (b) conventionally at 1100°C and (a1)-(a10) magnified images of grain boundaries marked in circles at (a) [22].…”
Section: Sintering Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…4a, we can see that at 1400 1C the main migration mechanism is grain boundary diffusion because q 4 3, and that volume diffusion has taken effect at 1410 1C but grain boundary diffusion still plays a main role for q ¼ 2.82 7 0.03 close to 3. Since grain boundary diffusion has little effect on grain growth [6,7,14] and volume diffusion is connected with grain growth [9], the grain growth rate plot (Fig. 3) below 1410 1C is very placid.…”
Section: Resultsmentioning
confidence: 98%
“…High densities and homogeneous microstructures with small grain size have been obtained for BaTiO 3 [12], Y 2 O 3 , [13,14] cZrO 2 , [15,16], and ZnO [17] ceramics sintered by the two-step method that consists of the individual stages grain growth and densification.…”
Section: Introductionmentioning
confidence: 98%